Determination of Gonadal Sperm/Spermatid Reserves in Shikabrown Breeder Cocks - Obidi, J.A.; Onyeanusi, B.I.; Ayo, J.O.; Rekwot, P.I.; Dzenda, T. (International Journal of Poultry Science, 2008)
The objective of this study was to determine gonadal sperm/spermatid reserves in Shikabrown breeder cocks. Five cocks, each of Shikabrown White and Shikabrown Red, were slaughtered after one year of evaluation of seminal characteristics. To determine testicular integrity of the breeder cocks, left and right testes from each slaughtered samples were carefully dissected out of the abdomen and marked accordingly. Each testis weight, length and volume were measured, followed by the determination of gonadal sperm/spermatid reserves. The mean testicular lengths for Shikabrown White were 4.22 ± 0.03cm and 3.98 ± 0.04cm for the right and left testes, respectively; while that for Shikabrown Red were 4.40 ± 0.1cm and 4.44 ± 0.09cm for right and left testes, respectively. The mean testicular weight of Shikabrown Red cocks was significantly (P < 0.01) higher than that of Shikabrown White cocks (12.39 ± 0.76g and 10.23 ± 0.25g, respectively). The mean gonadal sperm/spermatid reserves (x 109 per ml testis) for the right testes in Shikabrown White and Shikabrown Red cocks were 57.6 ± 5.6 and 103.2 ± 22.3 (P < 0.01), respectively, while those of the left testes were 84.8 ± 18.2 and 209.4 ± 95.1, respectively. The left mean gonadal sperm/spermatid reserves in Shikabrown Red strain was statistically (P < 0.01) higher than Shikabrown White strain. This study suggests: I) that there are strain differences in testicular function of the breeder cocks and ii) that there are differences in spermatogenic capacity between the right and left testes in breeder cocks.